Orange opals from Buriti dos Montes, Piauí: solid inclusions as genetic guides - Marques,Gisele Tavares (2015)
Orange opals from Buriti dos Montes (Piauí, northeastern Brazil) have gemological properties that favor their use as jewelry; these characteristics include their colors, transparency, relatively high stability and hardness. The exotic content of solid inclusions provides greater beauty to the opals of this region. These opals originated from hydrothermal processes and are found mainly as veinlets and veins in the sandstones of the Serra Grande Group, sectioned by diabase dikes and sills of the Sardinha Formation. Solid inclusions, such as bubbles, botryoidal aggregates, dendrites, and nodules, among others, consist mainly of kaolinite, hematite/goethite and quartz and influence the chemical composition of opals. Intense zoning of quartz crystals and high values of Ba and Fe suggest that opal deposits were formed in a hydrothermal environment. Diabase dykes could have been responsible for heating the hydrothermal fluids. Sandstones, rich in aqueous solutions, also contributed to the available silica for the saturation of these solutions, and fractures enabled the migration and entrapment of hydrothermal fluids, resulting in the mineralized veins.